The Relationship between the Quality of Prolanis Services and the Loyalty of Prolanis Participants at the Kedungwuni II Health Center in 2026 - Kaisyah Lathifatul Hanifah; Yuniarti Yuniarti; Teguh Irawan (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2026)
The Chronic Disease Management Program (Prolanis) is a BPJS Kesehatan initiative designed to improve the quality of life of patients with chronic diseases through continuous healthcare services. However, its implementation at primary healthcare facilities remains suboptimal due to low participant activity and service quality, which may affect participant loyalty. This study aimed to analyze the relationship between Prolanis service quality and participant loyalty at Kedungwuni II Public Health Center in 2026. A quantitative correlational study with a cross-sectional design was conducted involving 76 respondents selected through probability sampling. Data were collected using questionnaires on service quality and participant loyalty and analyzed using the Spearman Rank test (α = 0.05). The results showed that 56.6% of respondents perceived Prolanis service quality as poor, while 51.3% were categorized as less loyal. Significant relationships were found between the dimensions of reliability (p=0.000), responsiveness (p=0.000), and empathy (p=0.000) and participant loyalty. In contrast, tangibles (p=0.251) and assurance (p=0.436) were not significantly associated with loyalty. Improving reliability, responsiveness, and empathy is recommended to enhance participant loyalty.